A cross-cultural comparison of dual career environments for elite athletes in Switzerland, Denmark, and Poland - Kuettel, A.; Christensen, M. K.; Zysko, J.; Hansen, J. (International Journal of Sport and Exercise Psychology, 2020)
The purpose of this qualitative study is (a) to explore and compare the beliefs and values of the stakeholders working in different national dual career environments, and (b) to enhance the understanding of the relationship between athletes` dual career trajectories and the respective environments. Twelve semi-structured interviews with key informants involved in dual career from Switzerland, Denmark, and Poland were used to discussing benefits, obstacles and best practices of their national dual career settings. Interviews were content analysed in a deductive-inductive way using (Schein, E. H. (2010). Organizational culture and leadership (4th ed.). San Francisco, CA: John Wiley & Sons) cultural framework. Besides the differences in support for elite athletes in higher education across the national contexts, the key informants expressed divergent values and attitudes, which were due to their opinions on how dual careers should be organised. These values were found to be linked to the ideologies of the welfare regimes in the given country. Since dual career practices and programmes are based on different underlying basic assumptions in the three contexts studied, divergent dual career trajectories are proposed to athletes as the typical way to combine elite sport and education. Based on the results of our cross-cultural comparison, we assert that culture is not only an influential but also a constituting factor in the development of dual career environments. Thus, we propose a culturally sensitive approach towards the dual career of athletes and invite professionals (e.g. coaches, career advisors, and educational programme leaders) to critically reflect on their contextualised values about how to support dual career athletes.